Analysis of Distributional Equity of Public Physical Infrastructure in Pakistan - ayza, Ayza Shoukat; Muhammad Abdullah (Journal of Peace, Development and Communication, 2021)
The significance of public physical infrastructure (PPI) is hard to brush aside. Whereas, misallocation of PPI tends to overshadow the growth as well as creates disruption and unrest among the territories. The theory of public choice proposes that embracing the equity effect in distribution of PPI can improve overall economic growth as well as concord the economic well-being. The current study has empirically tested the equity approach in distribution of PPI among the provinces of Pakistan. We have adopted an innovative approach by analyzing the equity principle. Panel data for provinces of Pakistan has been employed for the period of 1988-2018. The stationarity of the variables has been checked through Levin, Lin & Chu test. As we get mixed order of integration, panel ARDL is used to estimate the results. The study concludes that the distribution of PPI in provinces of Pakistan is based on the equity principle. Whereas the other economic indicator efficiency is traded off against equity. The short run negative and significant ECT term also confirms the existence of long run relationship between variables. These results ensure that despite the heterogenous characteristics of each province, the distribution of PPI is done to equalize the living standards across the country. Key words: Public choice, Public physical infrastructure, Equity approach and ARDL